Canaliculitis With Isolation of Myroides Species. (May 2017) - Ali, Mohammad Javed; Joseph, Joveeta; Sharma, Savitri; Naik, Milind N.
Abstract : Genera Myroides belongs to the family flavobacteriaceae and are a group of Gram-negative bacilli which are nonmotile, nonfermentative, and oxidase positive. Myroides spp. are routinely found in the soil and water and rarely cause infections in the immunocompromised patients and are usually multidrug resistant. The authors describe the first case of chronic canaliculitis caused by Myroides spp. along with a brief review of literature. The patient responded to nonincisional canalicular curettage and topical moxifloxacin. Abstract : The authors present a case of Myroides canaliculitis.